Antenatal education for labour and postpartum pain: A scoping review of content, delivery approaches, evidence gaps, and lived experiences - Elliot Sloyan; Elizabeth Leddy; Carol Clark; Sinéad Dufour; Rosie Harper; Alex Dunford; Ömer Elma (PLoS ONE, 2026)
Background Pain during labour and the postpartum period is a complex and multidimensional experience. Antenatal education programmes aim to prepare individuals for childbirth and early parenthood; however, the extent to which these programmes address labour and postpartum pain management, and how women experience this education, remains unclear. This scoping review aimed to map the content, delivery characteristics, and evidence gaps of antenatal education programmes addressing labour and postpartum pain, including women’s lived experiences. Methods This review was conducted in accordance with PRISMA-ScR and Joanna Briggs Institute guidelines. The protocol was registered with the Open Science Framework (6597j). Twelve electronic databases were systematically searched in November 2025. Quantitative, qualitative, and mixed-methods primary studies examining antenatal education programmes with a focus on labour or postpartum pain were included. A narrative synthesis was undertaken to map intervention content, delivery approaches, and pain-related outcomes and experiences. Results A total of 5,959 records were identified from the search strategy. A total of 17 articles met the eligibility and inclusion criteria, including seven randomised controlled trials, seven quasi-experimental studies, one pre-post study, and two qualitative studies. The content and structure of antenatal education interventions between studies was heterogenous. Common themes included the distinction between “true and false labour pain” and breathing exercises. Qualitative findings highlighted women’s perceived improvements in pain coping, confidence, sense of control, and use of non-pharmacological strategies during labour. Conclusion Antenatal education programmes contain limited information on labour and postpartum pain management, with little consistency across interventions. While non-pharmacological strategies appear valuable in supporting coping and confidence during labour, pain mechanisms and postpartum pain remain under-addressed. Incorporating pain-focused education such as pain neuroscience principles may enhance antenatal education and support more effective pain management. Further research is required to develop and evaluate consistent, evidence-based antenatal education approaches that address both labour and postpartum pain.